2021
DOI: 10.1186/s12906-021-03262-w
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activities of Aspiletrein A, a steroidal saponin from Aspidistra letreae, on non-small cell lung cancer cells

Abstract: Background Lung cancer is one of the leading causes of death worldwide due to its strong proliferative and metastatic capabilities. The suppression of these aggressive behaviors is of interest in anticancer drug research and discovery. In recent years, many plants have been explored in order to discover new bioactive secondary metabolites to treat cancers or enhance treatment efficiency. Aspiletrein A (AA) is a steroidal saponin isolated from the whole endemic species Aspidistra letreae in Viet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…In this study, we found that AA, a steroidal saponin from A. letreae , exhibited a potent apoptosis-inducing effect in NSCLC cells. Anticancer activities of AA have been previously reported [ 24 ], and this study also provides that AA has greater toxicity to the lung cancer cell lines than normal bronchial epithelial BEAS-2B cells, of which the selective index (SI) values were approximately 1.6–2.6-folds ( Table S1 ). Furthermore, we revealed the first evidence of the underlying molecular mechanism regarding the apoptosis-inducing effect.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In this study, we found that AA, a steroidal saponin from A. letreae , exhibited a potent apoptosis-inducing effect in NSCLC cells. Anticancer activities of AA have been previously reported [ 24 ], and this study also provides that AA has greater toxicity to the lung cancer cell lines than normal bronchial epithelial BEAS-2B cells, of which the selective index (SI) values were approximately 1.6–2.6-folds ( Table S1 ). Furthermore, we revealed the first evidence of the underlying molecular mechanism regarding the apoptosis-inducing effect.…”
Section: Discussionsupporting
confidence: 67%
“…Several anticancer drugs obtained from natural sources show versatile biological effects. Aspiletrein A (AA) is a steroidal saponin isolated from Aspidistra letreae [ 24 ] that exhibits various pharmacological activities, such as diuretic, expectorant, and antiviral and antifungal actions [ 25 ]. The cytotoxicity of this compound against several cancer types, including breast, cervical, lung, and gastric cancer cell lines, has also been reported [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the plants of the Aspidistra genus, discovered in Vietnam 6 , contain many active components, such as saponin, coumarin, and isoflavones 7 , 8 , with various demonstrated pharmacological activities, including antibacterial, antifungal, antitumor, and antiviral 7 10 . A previous study reported that Aspiletreins, mainly three steroidal saponins, exhibited cytotoxicity in breast, cervical, hepatocellular, gastric, and lung cancer cells 8 , 11 . These three steroidal saponins contain different sugar moiety side chains located at C3, suggesting distinct potencies (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…These three steroidal saponins contain different sugar moiety side chains located at C3, suggesting distinct potencies (Table 1 ). The mechanistic investigation demonstrated that Aspiletrein A (AA) could suppress lung cancer metastasis by inhibiting protein kinase A (Akt) signaling 11 . However, the molecular targets of Aspiletreins B and C (AB and AC, respectively) have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%